NANO-INFLUENCERS ON SOCIAL MEDIA AS AN EFFECTIVE AND EFFICIENT MARKETING PROMOTION - Prayudi, Dicki; Oktapiani, Renny (Universitas Sahid, 2023)
Social media marketing is one of the items developed by marketers for a practical marketing style. Social media is considered capable of reaching consumers quickly and can introduce products carefully. The aim of this research is to determine the distribution of nano-influencers as the most efficient and effective marketing tool, as well as the most numerous class of influencers. The research method uses a literature review, to describe the paradigm of social media marketing and various influencers. The literature review also describes ten leading research on nano-influencer objects. In addition, the preparation of nano-influencer indicators was also carried out by experts, as was observing and approving these indicators for influencers. The results of the study show that there are ten indicators based on a review of the bibliography that are similar to the opinions of experts. As well, there are two indications that have not yet received approval based on influencer observations, namely nano-influencers have presence and can respond to expectations. The third source is research by adopting nano-influencers as the most effective and efficient influencers.